Patients in general practice share a common pattern of symptoms that is partly independent of the diagnosis. (3rd April 2021) - Kjeldsberg, Mona; Tschudi-Madsen, Hedda; Mdala, Ibrahimu; Bruusgaard, Dag; Natvig, Bård
Abstract: Objective: To describe self-reported symptoms among patients in general practice and to explore the relationships between symptoms experienced by patients and diagnoses given by general practitioners. Design: Doctor–patient questionnaires focusing on patients' self-reported symptoms during the past 7 days and the doctors' diagnoses. Setting: General practices in urban and suburban areas in Southeast Norway. Subjects: Forty-seven general practitioners who included 866 patients aged ≥18 years on a random day in practice. Results: The most frequently reported symptoms were tiredness (46%), lower back pain (43%), neck pain (41%), headache (39%), shoulder pain (36%), and sleep problems (35%). Women had a significantly higher prevalence than men for 16 of 38 symptoms ( p  < 0.05). The mean number of symptoms was 7.5 (range, 0–32; women, 8.1; men, 6.5, p  < 0.05). Regression analysis showed that patients who received a social security grant had 59% more symptoms than those who were employed and that people with asthenia and depression/anxiety had 44% and 23% more symptoms, respectively than those with all other diagnoses. The patterns of symptoms reported showed similar patterns across the five most prevalent diagnoses. Conclusions: Patients in general practice report a number of symptoms and share a common pattern of symptoms, which appear to be partly independent of the diagnoses given. These findings suggest that symptoms are not necessarily an indication of disease. KEY POINTS: Patients consulting general practitioners have a high number of self-reported symptoms. The most frequent symptoms are tiredness, lower back pain, neck pain, headache, shoulder pain, and sleep problems. Patients diagnosed with asthenia and depression/anxiety report the highest number of symptoms. Selected diagnoses show similar patterns in symptom distribution. Symptoms are not necessarily an indication of disease.